UTILIZATION OF F-AHP METHOD IN BRI FOR GIVING SELECTION OF KUR - Meiyanto Eko Sulisyo; Ristu Saptono (Jurusan Teknik Informatika, 2016)
Bank Rakyat Indonesia (BRI) is a business entity which collects funds from the public in the form of deposits and distribute to the public in the form of the People 's Business Credit (KUR) or loan. Along with over time after KUR realized, there is no doubt BRI will be faced with the problems of risk, namely the risk of KUR problematic. There are several methods that can be used in making a decision to be able to solve the problem include the Analytical Hierarchy Process (AHP).AHP is used when the decision involves many factors, where the decision had difficulty in making the weight of each factor. Despite this problem the use of AHP in Multiple Criteria Decision Making (MCDM) approach has less to cope with uncertainties taken by decision-makers, when it should give a definite value in the pairwise comparison matrix therefore, to overcome the weaknesses of the existing AHP then developed a method namely Fuzzy Analytic Hierarchy Process (F-AHP). F-AHP method is the combination between fuzzy AHP approach. The results of research conducted using the Fuzzy Analytic Hierarchy Process (F-AHP) has a 100 % accuracy this is evidenced by the results obtained together with the calculation of banking. Calculation banking mention of 20 customers, acquired 14 accepted and rejected 6.